Distribution, incidence and detection of a Potyvirus on chilli from eastern Uttar Pradesh - R.K. SINGH; P.P. UPADHYAYA, SATYA PRAKASH, S.J. SINGH (Indian Phytopathology, 2002)
A virus disease of chilli causing dark green mottling and distortion symptoms on leaves was observed in chilli growing areas of eastern U.P. during survey in 1997 and 1998. The disease was distributed throughout eastern U.P. and the incidence ranged from 5-75%. The highest incidence up to 50% and 75% were recorded from Gorakhpur during the years 1997 and 1998, respectively. The virus was identified on the basis of symptomatology, host range, transmission, physical properties, electron microscopy and serology. The virus was transmitted by mechanical sap inoculation and also by aphids viz. Aphis gossypii, A. craccivora and Myzus persicae. The thermal inactivation point was between 60-65Â°C, dilution end point between 1:5000-1:10000 and longevity in vitro between 2-4 days at room temperature. In DAC-ELlSA, the virus reacted positively with antiserum to Chilli veinal mottle virus (CVMV). In host range studies, the virus produced systemic symptoms on Capsicum annuum L. (vars. Suryamukhi, Pusa Jwala, California Wonder, Gauribidanur and Byadagi Kaddi), C. microcarpum, C. pendulum, C. frutescens L. Tabasco, Datura stramonium, Lycopersicon esculentum Mill. (var. Pusa Ruby), Nicotiana glutinosa L., N. sylvestris and N. tabacum (vars. White Burley, Samsun and Xanthi). Electron microscopy of leaf -dip preparations from infected chilli leaves revealed filamentous particles measuring 750x12 nm. Ultrathin sections of infected leaf revealed cytoplasmic cylindrical inclusions as "pinwheels". Based on these studies, the causal was identified as a Potyvirus related to Chilli veinal mottle virus.